2021
DOI: 10.3390/polym13234056
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl Cellulose Hydrogel from Biomass Waste of Oil Palm Empty Fruit Bunch Using Calcium Chloride as Crosslinking Agent

Abstract: Carboxymethyl cellulose (CMC) is modified cellulose extracted from oil palm empty fruit bunch (OPEFB) biomass waste that has been prepared through etherification using sodium monochloroacetate (SMCA) in the presence of sodium hydroxide. In this research, CMC hydrogel was prepared using calcium chloride (CaCl2) as the chemical crosslinker. Throughout the optimization process, four important parameters were studied, which were: (1) CMC concentration, (2) CaCl2 concentration, (3) reaction time, and (4) reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…The second decrease in mass is observed in the range of about 300 to 500 °C. This reduction in mass could be related to the degradation of the cellulose backbone in the CMC structure as well as the cleavage of peptides in SF 41,42 . After 500 °C the mass of the GO-CMC hydrogel/SF/Fe 3 O 4 nanobiocomposite is reduced at a very low speed and eventually, about 30% of the mass remains at 1200 °C due to the inorganic parts.…”
Section: Tg Analysismentioning
confidence: 99%
“…The second decrease in mass is observed in the range of about 300 to 500 °C. This reduction in mass could be related to the degradation of the cellulose backbone in the CMC structure as well as the cleavage of peptides in SF 41,42 . After 500 °C the mass of the GO-CMC hydrogel/SF/Fe 3 O 4 nanobiocomposite is reduced at a very low speed and eventually, about 30% of the mass remains at 1200 °C due to the inorganic parts.…”
Section: Tg Analysismentioning
confidence: 99%
“…Compared with the control, the cumulative infiltration of soil treated with 0.2, 0.4, 0.6, and 0.8 g/kg CMC increased by 8.63%, 15.78%, 20.72%, and 17.75%, respectively, when the preset depth (30 cm) was attained. This was due to the fact that CMC improved the soil pore structure and increased the number of soil fine pores, thereby improving the water holding capacity of each soil layer and boosting the soil cumulative infiltration [ 10 ]. This suggested that the application of CMC could introduce more free water into the soil fine pores, which was beneficial to the full leaching of soil salinity.…”
Section: Resultsmentioning
confidence: 99%
“…CMC is usually an anionic polymer compound prepared by the reaction of natural cellulose with caustic soda and monochloroacetic acid, with molecular weight ranging from tens of millions to millions. Moreover, CMC is a water-soluble polymer with a high viscosity that can improve and sustain soil structure while also increasing cohesion between soil particles [ 10 , 11 ]. Many academics have used it to improve soil structure and water retention performance because of its wide availability, nontoxicity, and easy degradation by microorganisms in the soil [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…OPEFB can be used as a feedstock for the production of multiple products as bioenergy resource, materials in polymer composites for energy absorption, and as a nanocellulose material in hydrogel production [2] . Carboxymethyl cellulose (CMC) hydrogel is modified cellulose extracted from OPEFB biomass waste can be used in various applications such as drug delivery systems, industrial effluent, food additives, heavy metal removal, and many more [3] . The compounds in OPEFB lignin such as vanillin, syringaldehyde, and p-hydroxybenzaldehyde promise as a nutraceutical and health supplement especially in pharmaceutical and food supplement industries [4] .…”
Section: Data Descriptionmentioning
confidence: 99%